The health-related quality of life in patients with prostate cancer managed with active surveillance using the Expanded Prostate Cancer Index Composite survey: Systematic review and meta-analysis. Issue 2 (3rd April 2022) - Abdelhafez, Ahmed; Hosny, Khaled; El-Nahas, Ahmed R.; Liew, Matthew
ABSTRACT: Objective: To examine the health-related quality of life (HRQoL) of patients with prostate cancer managed with active surveillance (AS) compared with those who receive definitive treatment using the Expanded Prostate Cancer Index Composite (EPIC) Survey. Methods: We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and searched PubMed and ScienceDirect for articles published between April 2010 and April 2020. Eligible studies reported original data on the HRQoL of men undergoing AS for prostate cancer, including studies comparing AS to curative methods particularly radical prostatectomy, radiotherapy, and brachytherapy. Results: We identified nine eligible articles, all were non-experimental observational studies of which seven were longitudinal and two were cross-sectional studies. The EPIC questionnaire was the main instrument used in all studies to assess the HRQoL. AS was noted to show the highest calculated mean score among management groups in all comparative studies at study endpoints including cross-sectional studies (95% confidence interval 2.17–5.75, P < 0.001). The maximum score deterioration for patients who were managed with AS in all studies was only 7.5 points (12.2%) after 2 years follow-up. AS had the least mean score decline among all management groups. Patients with a normal testosterone level were found to have high HRQoL scores. The number of prostate biopsies did not correlate with the HRQoL score. Conclusion: Patients with prostate cancer managed with AS report less impacts on their HRQoL compared to patients who receive definitive treatments. However, further high-quality research with long-term data are required to help both the patient and the physician in making a well-informed management decision.